2010
DOI: 10.1089/acm.2009.0208
|View full text |Cite
|
Sign up to set email alerts
|

Extremely High-Frequency Therapy in Oncology

Abstract: In spite of the fact that not all mechanisms underlying effects of EHF therapy are known as yet, this therapeutic modality has been shown to have great potential in clinical oncology from studies performed in Eastern Europe and Russia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 5 publications
1
10
0
2
Order By: Relevance
“…Previously studies demonstrated millimeter wave radiation in treatment for various types of malignant tumors. The main indications for this therapy are prevention of metastases, relapses, and dissemination of the tumor; prevention and treatment of side-effects and complications from chemotherapy and radiotherapy; and treatment of the paraneoplastic syndrome (6,7). However, the molecular mechanism of millimeter wave radiation therapeutic effect is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Previously studies demonstrated millimeter wave radiation in treatment for various types of malignant tumors. The main indications for this therapy are prevention of metastases, relapses, and dissemination of the tumor; prevention and treatment of side-effects and complications from chemotherapy and radiotherapy; and treatment of the paraneoplastic syndrome (6,7). However, the molecular mechanism of millimeter wave radiation therapeutic effect is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction of biological cells with millimeter waves (MMW) has been under investigation for several decades as potential cancer therapy. MMW irradiation has been in wide clinical use, mostly in Eastern Europe, for the treatment of more than 50 diseases including cancer, and it was claimed that treatment was successful in more than three million patients [Rojavin and Ziskin, 1998; Teppone and Avakyan, 2010].…”
Section: Introductionmentioning
confidence: 99%
“…MMWs can be used as a monotherapy or in combination with other treatment methods. As an adjunct therapy, they are widely used to protect the immune system from the toxic effects of chemo-and radiation therapy in the treatment of cancer [3,7].…”
Section: Introductionmentioning
confidence: 99%